Twist sensor based on axial strain insensitive distributed Bragg reflector fiber laser - Wo, Jianghai (2013)
A novel fiber-optic twist sensor based on a dual-polarization distributed Bragg reflector (DBR) fiber grating laser is proposed and experimentally demonstrated. By beating the signal between the two polarizations of the laser which operates at 1543.154nm, a signal of 30.78MHz in frequency domain is observed. The twist will change the fiber birefringence, and resulting in the beat frequency variation between the two polarization modes from the fiber laser. The result shows the beat frequency shifts as a Sinc function curve with the twist angle and both the measuring curve period and twist sensitivity depend on the twist length of the laser cavity. A high twist sensitivity of 6.68MHz/rad has been obtained at the twist length of 17.5cm. Moreover, the sensor is insensitive to the environmental temperature, as well as strain along the fiber axis with ultralow beat frequency coefficients, making temperature and axial strain compensation unnecessary.